1994
DOI: 10.2307/1591834
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enteritidis in Eggs from Commercial Chicken Layer Flocks Implicated in Human Outbreaks

Abstract: Eggs were cultured from four commercial chicken layer houses implicated in three human outbreaks of Salmonella enteritidis serotype enteritidis infection as part of the activities of the USDA-APHIS, VS, Salmonella enteritidis Task Force. Each house was part of a multiple in-line complex, ranging from three to seven houses. Houses were located on three separate farms, and each house contained between 50,000 and 80,000 chickens. S. enteritidis phage types 8, 13a, and 23 were isolated from samples taken from envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 3 publications
0
38
0
6
Order By: Relevance
“…14 However, it should be mentioned that Belgium has many laying hens compared to 15 neighbouring countries (Quinet, 2005). The European survey was based on environmental 16 sampling which is considered to be an accurate and representative indicator for the presence 17 of Salmonella in layer flocks and for the probability that hens would lay contaminated eggs 18 (Henzler et al, 1994;Kinde et al, 2005). The persistence of the pathogen in the intestinal 19 tract is more important when infection occurs in young chicks, since bacterial clearance 20 occurs more efficiently in adults.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, it should be mentioned that Belgium has many laying hens compared to 15 neighbouring countries (Quinet, 2005). The European survey was based on environmental 16 sampling which is considered to be an accurate and representative indicator for the presence 17 of Salmonella in layer flocks and for the probability that hens would lay contaminated eggs 18 (Henzler et al, 1994;Kinde et al, 2005). The persistence of the pathogen in the intestinal 19 tract is more important when infection occurs in young chicks, since bacterial clearance 20 occurs more efficiently in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling the hen house environment, when coupled with suitable cultural techniques, has proved a sensitive and cost-effective method of monitoring salmonella carriage and excretion by layer hens (Kradel & Miller, 1991;Henzler et al ., 1994), and there is good agreement between the level of environmental contamination and the level of internal egg contamination and associated human disease (Altekruse et al ., 1993;Henzler et al ., 1994Henzler et al ., , 1998Schlosser et al ., 1995;Mallinson et al ., 2000). The sensitivity of environmental sampling varies between sample types (Davies & Wray, 1996), and in caged layers samples taken from egg belts, from dust close to birds or cage stacks and from naturally accumulated pooled chicken faeces on droppings belts or scrapers have proved especially useful .…”
Section: Introductionmentioning
confidence: 99%
“…Egg 3 In addition, it has been reported that Salmonella present on the egg shell surface enters the egg through stomas or cracks (Cho, 2011;Henzler et al, 1994;Jang et al, 1999). As evident from the test results conducted in the present study, bacteria were isolated from both egg contents and egg shells, identical results were obtained from antibiotic resistance tests, and the isolates showed more than 99% homology.…”
Section: Resultsmentioning
confidence: 99%